Heart Disease Detection using Autoencoder - Rajeswari, D; Thangavel, K (International Journal of Computer Sciences and Engineering, 2025)
Early detection of heart disease can be achieved by high disease prediction and diagnosis efficiency. Machine learning techniques can help the medical expert in decision making for providing the best treatment. In this paper, an autoencoder neural network classifier is developed for the classification of heart disease medical data sets. The autoencoder were trained to properly classify the clinical data. The proposed classifier is tested on heart disease data sets namely Cleveland and Statlog obtained from the UCI repository and also compared with conventional classification techniques namely Support Vector Machine, Random Forest, K-Nearest Neighbour, Naïve Bayes to concerning its outperformance. Experimental results show that the autoencoder neural network clas¬sifier offers much better classification accuracy, precision, recall and f-measure rates when compared with other conventional methods. The proposed method presents itself as an easily accessible and cost-effective alternative to traditional machine learning methods which are used for the diagnosis. In this study, the implementation of the developed model can potentially support in reducing heart disease among patients